Pengembangan Ekowisata melalui Strategi Bauran Komunikasi Pemasaran (Marketing Communication) - Andhika Permata; Haililah Tri Gandhiwati Gandhiwati; Timotheus Lesmana Wanadjaja (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2023)
The Thousand Islands is a district area that is part of the city of Jakarta. The Thousand Islands consist of 110 islands, of which 16 are resident islands and resort islands or islands that are intended as tourist destinations (Jakarta.go.id, 2019). The Thousand Islands have a variety of beach and marine tourism attractions. As one of the islands in the Jakarta Province area, the existence of marine-based Seribu Islands tourism is unique in its own right. Based on data from the Seribu Islands Tourism and Creative Economy Sub-agency, only 30% of Jabodetabek people know the tourist area well, which is part of the DKI Jakarta area (CNN Indonesia, 2019). The research approach used in this study was qualitative research. The selection of informants was carried out using non-probability techniques due to suitability in the context of qualitative research. Of the various marketing communication mix activities carried out, online publications are still not optimized. In addition, supporting facilities are needed, such as transportation and lodging that are proper and CHSE certified, so that tourists who visit have a different experience and can deliver a massive word-of-mouth campaigns.